Efektivitas Penggunaan Aplikasi Open Source dalam Pembelajaran Matematika Komputer - setiawan, I Made Dedy (UNIB Press, 2024)
Mathematics is an important aspect in the higher education curriculum, especially in the field of computer science. The role of mathematics such as calculus, algebra and statistics is urgent for current technological developments. So far, computer mathematics learning in INSTIKI classes has not utilized open source-based applications. For this reason, innovation is needed in mathematics learning, one of which is by utilizing the Geogebra application. The aim of this research is to determine the effectiveness of using open source applications in computer mathematics learning. This research follows a quantitative descriptive research design involving a sample of 50 respondents selected purposively. Data was collected using a questionnaire consisting of 20 statement items and divided into three aspects, namely suitability of the material, convenience and attractiveness. The data was then analyzed descriptively quantitatively. The research results showed that from the suitability aspect of the material, the most dominant answer was obtained, namely strongly agree at 57%, from the convenience aspect, the most dominant answer was obtained, namely agree at 43%, while from the attractiveness aspect, the most dominant answer was obtained, namely strongly agree at 54%. From the research results it can be concluded that the use of open source applications is quite effective in learning computer mathematics.